Specyfika pracy reportera w telewizji newsowej na przykładzie TVN24 - Borowski, Piotr (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2013)
The author describes the specifics of work in a large TV newsroom and the job of a TV reporter, based on his own experience. He also emphasizes the role of speed and the reliability of news editing, and explains how to organize work in the newsroom.